Pengelolaan Dana Wakaf Produktif Melalui Investasi Syariah Perspektif Hukum Islam - Ziyad Ulhaq; Firda Anidiyah (Fakultas Syariah dan Ekonomi Islam Institut Ilmu Al-Qur'an (IIQ) Jakarta, 2020)
This study aims to analyze the strategy for managing productive waqf funds through sharia investments practiced in the ACT Global Waqf (Fast Action Response) and analyze whether the mechanism for managing productive waqf funds for the Global Waqf ACT (Fast Action Response) in Islamic investments is in accordance with Islamic law. The results showed that the practice of managing and utilizing ACT-GWF productive waqf funds was stated to have been made from the perspective of Islamic law, which can be seen in terms of management avoiding usury, and their utilization was in accordance with Islamic law, namely being able to distribute its benefits to the public interest, especially in the field of humanity and education.